التداوي بالأعضاء والأجزاء الآدمیّة في المنظور الإسلامي (Journal of the College of Education for Women, 2019)
In a controversy between the intellectuals and doctors of Legal and Islamicscholars, about the legality of medication organs and human parts, comes thisstudy, in order to reveal the controls of Islamic in that issue above, and to show theeffectiveness of Islam and its role, and the extent needed in the treatment ofproblems intractable, and the resolution of the controversy in the case above, inorder to preserve the human dignity and the right integration of physical, andprevents from Aptmalh, and included in the financial contracts, and to achieve thatgoal, presented the study to the issue of the rule of medication and look to Islam tohim, and the rule of therapeutics in human organs, and the views of Almjizin andAlmanaan for that and their evidence, and the balance between those views, andindicate the most correct of them. The study concluded that reducing thepermissible tolerance in organ medication, and the prohibition of sale or gift ofhuman organs.